Enhanced diagnosis and severity assessment of carpal tunnel syndrome using combined shear wave elastography and cross-sectional area analysis: A prospective case-control study. - Jaewon Kim; Min-Wook Kim; Jae Min Kim (PLoS ONE)
Carpal tunnel syndrome (CTS) is a prevalent neuropathy resulting from median nerve compression, typically diagnosed through electrodiagnostic studies. Shear wave elastography (SWE) has emerged as an essential imaging technique, especially in evaluating tissue elasticity, which could enhance the diagnosis and severity assessment of CTS. This study aimed to examine the combined effect of the median nerve's cross-sectional area (CSA) and elasticity assessed through SWE in diagnosing CTS and evaluating its severity. A total of 50 participants were involved in this prospective study, with 99 wrists analyzed (51 affected by CTS and 48 normal controls). Measurements of both CSA and elasticity were taken at the carpal tunnel inlet. The findings indicated that CSA and elasticity were considerably higher in CTS patients than in the controls. The combined parameter of CSA ×  elasticity outperformed other measures for differentiating between normal and CTS cases (Area Under the Curve 0.91, sensitivity 0.90, specificity 0.83, cutoff 753.7 kPa·mm²). This combined metric also showed potential for distinguishing CTS severity levels, particularly between mild and severe cases. Although CSA and elasticity alone had limitations in severity classification, their combined values illustrated significant distinctions across severity levels. Integrating SWE with CSA notably improves diagnostic accuracy for CTS and shows potential for severity grading. This approach offers a more detailed evaluation of the structural and mechanical changes in the median nerve, potentially enhancing both the diagnosis and management of CTS.